Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawan Bagian Produksi Pada PT Glico Wings Karawang - Shepia; Rustomo; Yanto Lesmana (Politeknik Raflesia Press, 2026)
The enduring viability of businesses operated by Micro, Small, and Medium Enterprises (MSMEs) hinges on their capacity to evolve with shifting market dynamics, their integration of technological advancements, their understanding of financial principles, and the backing they receive from both governmental bodies and local communities when navigating diverse economic obstacles. The central aim of this research endeavor was to scrutinize the effects of financial understanding, digital proficiency, and the adoption of financial technology on the long-term stability of MSMEs operating within the Sumbawa Regency. This research employed a quantitative methodological framework, focusing on a total population of 1,362 MSME business owners located within the Sumbawa Regency area. The sample selection process involved a total sampling strategy, with the quantity of participants determined via the Slovin formula, which resulted in the acquisition of responses from precisely 100 individuals. Information was gathered through the distribution of questionnaires utilizing a Likert scale, ranging from a value of 1 to 4. The data analysis was executed via the application of multiple linear regression methodologies. The findings derived from this study revealed that having a grasp of financial concepts, being digitally literate, and utilizing financial technology all exert a beneficial and notable impact on the sustained performance of MSMEs throughout the Sumbawa Regency..